2008
DOI: 10.1590/s1516-35982008000300018
|View full text |Cite
|
Sign up to set email alerts
|

[No Title Available]

Abstract: RESUMO -Objetivou-se, com este estudo, verificar as diferenças nas características da carcaça, assim como nos parâmetros qualitativos da carne de novilhos jovens alimentados com dietas contendo silagem de grão úmido de milho ou sorgo.Foram utilizados dois tratamentos experimentais, nos quais a dieta total possuía como ingrediente energético principal a silagem de grão úmido de milho (TMU) ou a silagem de grão úmido de sorgo (TSU). Trinta e seis novilhos inteiros F1 Red Angus × Nelore com 8 meses de idade e pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
1
0
1
Order By: Relevance
“…The tenderness values found in all treatments are within the range considered as tender meat (below 4.6 kgf; Shackelford et al, 1991) and have been reported in other studies under similar production system, genetic group and age (Igarasi et al, 2008;Rubiano et al, 2009). The values found among all treatments analyzed for sarcomere length are within the natural variation (1.3-2.1 μm) found in tender meat (Starkey et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The tenderness values found in all treatments are within the range considered as tender meat (below 4.6 kgf; Shackelford et al, 1991) and have been reported in other studies under similar production system, genetic group and age (Igarasi et al, 2008;Rubiano et al, 2009). The values found among all treatments analyzed for sarcomere length are within the natural variation (1.3-2.1 μm) found in tender meat (Starkey et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…The lack of grain type effect on thawing, cooking and total losses have already been reported by Igarasi et al (2008), who evaluated the meat quality of steers fed wet corn or sorghum grains. Kazama et al (2008) also did not observe effect of different types of energy concentrates on thawing and cooking losses in beef.…”
Section: Discussionmentioning
confidence: 72%
“…Igarasi et al (19) em experimento com bezerros machos inteiros F1 Red Angus × Nelore, em confinamento recebendo dieta total com silagem de grão úmido de milho, como ingrediente energético principal, salientam esse tipo de processamento não altera as características físico-químicas de carcaças e maciez de carne.…”
Section: Figuraunclassified